Budidaya Maggot Sebagai Solusi Penanganan Sampah Organik Rumah Tangga Desa Bumiaji Kota Batu - Naibaho, Ester Oktavia; Juita, Indah Rahmah; Fitri, Niken Nuraidi; Herawati, Erlyta; Priyanto, Moh. Wahyudi (Jurnal Ilmiah Pangabdhi, 2025)
The problem of household organic waste management in Bumiaji Village, Batu City is increasing along with the cessation of the 3R TPS operation and the limited availability of final disposal sites. Waste burning and manual landfilling have a negative impact on the surrounding environment. The majority of people are unable to manage waste properly and according to data from the Central Statistics Agency 2020, waste originating from households is around 60% of waste, in this case if households are unable to manage waste, it will accumulate. Waste reduction must be carried out as much as possible from the source, namely reducing the amount of waste generated, increasing the amount of recyclable waste, or increasing waste that can be reused or better known as the 3R system. This community service aims to provide education and implement Black Soldier Fly (BSF) maggot cultivation as a solution for organic waste management. The methods used in this service are integrated maggot cultivation practices with chicken farming, socialization to PKK members and KBC communities, as well as monitoring and pre-post tests. The results of the activity show an increase in knowledge in organic waste management. This service shows that BSF maggot cultivation can be a sustainable waste management strategy and open up economic opportunities for the community. Further assistance is needed for the community to implement maggot cultivation as an organic waste management policy.